Kepuasan Kerja UMKM Giriloyo: Ditinjau dari Motivasi Ekstrinsik-Instrinsik, Lingkungan dan Beban Kerja - Heni Susilowati; Ignatius Soni Kurniawan; Nala Tri Kusuma (Universitas Muhammadiyah Palembang, 2025)
Purpose– This study aims to determine the influence of extrinsic motivation, intrinsic motivation, physical work environment, and workload on employee job satisfaction in UMKM (Micro, Small, and Medium Enterprises) located in Kampung Batik Giriloyo, Bantul. Design/methodology– A quantitative approach was employed. A total of 100 employees working at UMKM in Kampung Batik Giriloyo, Imogiri, Bantul, Yogyakarta, participated as respondents. Primary data were collected through questionnaires. Data were analyzed using multiple linear regression with the assistance of SPSS software. Findings - The results show that intrinsic motivation, physical work environment, and workload have a significant positive effect on employee job satisfaction, while extrinsic motivation does not have a significant effect. These findings suggest that UMKM managers should focus on strengthening intrinsic motivation, creating a conducive physical work environment, and managing workload proportionally to enhance employee job satisfaction, which in turn can improve overall performance and competitiveness